Storytelling as a Polifunctional Instrument of Modern Communication: Linguistic and Stylistic Features - Pyatetska , Olga (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article analyzes media instrument of modern communication, i.e. storytelling, which is widely used for commercial, advertising and corporate purposes to influence recipient's emotions, cognition and motivations. At the same time, storytelling based on real life facts is one of the most effective learning techniques that promotes linguistic competence and enables various communication tasks to be solved. Analysis of storytelling showed that it gained particular relevance due to the principles of submission the information in implicit form, unobtrusively influencing the audience, gaining its trust and loyalty, resulting in the recipients make their own decisions and draw appropriate conclusions. It is established that to reach a high level of influence on the target audience, a story must be true, emotional, relevant and new, contain an idea, a bright character or image, have a dynamic plot, often with a surprise effect, logical conclusion, intrigue till the end and (for electronic versions)be accompanied by quality content. Despite defined algorithms for story-building and typical content structures of its plot, there is a tendency to create storytelling outside the box. The main principle that determines the theme, ideas, specifics of language organization of stories is adaptation to the target audience. Separate analysis of direct-acting storytelling which has recently spread in social networks is given. Its purpose is to draw the reader's attention to current problems, influence the recipient's emotions and behavior with the help of verbal and non-verbal means. An example of such storytelling in Ukraine is the Ukraїner Media Project which helped to represent our country in a new way and realize the dreams of many ordinary citizens. The studying of different stories showed that storytelling uses such linguistic and stylistic means as emotionally coloured vocabulary which is typical for literary, mass media and colloquial functional styles, foreign words, jargon, slang expressions, phraseologisms, metaphors, personifications, rhetoric constructions etc. As for parts of speech, verbs are more frequently used because they intensify and dynamize the narrative.
Keywords: storytelling, target audience, linguistic and stylistic means, multifunctionality, communication, teaching and methodical techniques.